Educação para morte com idosos: uma visão naturológica sobre o profissional - Christofoletti, Flávia Cestaro (2011)
Population aging is a recurring topic today, and it causes constant concern about a population's quality of life. Quality of life is related to health, and it is defined as an individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards, and concerns, emphasizing the need of an integrative view of the human being. Naturology, as the field of knowledge that studies health from an integrated view of man, has the precept of working on prevention, maintenance and recovery of health through education. Based on an educative approach, the general aim of this study was to describe and analyse the work of education for death developed by professional workers at a Day Care Centre for the Old, and the specific aim was to identify how those workers are trained to educate for death, as well as to verify the ideological, religious, theoretical and technical positions they take and which ground their work with death. A qualitative research method was used and data were collected through a semi-structured interview, which was later submitted to content analysis. It was possible to verify the professionals' lack of preparation to attend the needs of the old, which reflects an academic development deficit. The major difficulties professionals face to deal with the subject were the age-related cognitive debilities as well as the social limitations to talk about the subject, and the ease observed was the various experiences of loss in an elderly person's life. The religious posture adopted by the participants was based on their own subjective experience with spirituality. Despite the lack of preparation to work with the subject, all the workers interviewed relate education for death to quality of life. It was found that in spite of the justifiable necessities for the work with death, several difficulties arise. Educative work aiming at prevention must be aggregated to all fields of knowledge on an integrative view of the human being